Changes of Serum IgG Glycosylation Patterns in Primary Biliary Cholangitis Patients - Zeng, Xiaoli; Li, Siting; Tang, Shiyi; Li, Xi; Zhang, Guoyuan; Li, Mengtao; Zeng, Xiaofeng; Hu, Chaojun (Frontiers in Immunology, 2021)
Objective: Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease whose diagnosis is based on autoantibody detection. This study aims to investigate the glycosylation profile of serum IgG in PBC patients using high-throughput lectin microarrays technology. Method: Lectin microarray containing 56 lectins was used to detect and analyze the expression of serum IgG glycosylation in 99 PBC patients, 70 disease controls (DCs), and 38 healthy controls (HCs). Significant differences in PBC from control groups as well as across PBC subgroups positive for various autoantibodies were explored and verified by lectin blot technique. Results: Lectin microarray detection revealed that compared to DC and HC groups, the specific glycan level of serum IgG sialic acid in PBC patients was increased. For each PBC subgroup, glycan levels of IgG mannose and galactose were decreased in AMA-M2 positive PBC patients compared to the AMA-M2 negative group. IgG acetylgalactosamine (GalNAc) and fucose were decreased in anti-SP100 positive patients. IgG galactose was increased in anti-GP210 positive patients. IgG mannose was decreased in ACA positive patients. Although the difference in overall sialic acid level was not observed using lectin blot, all results among PBC subgroups were confirmed by the technique. Conclusion: Lectin microarray is an effective and reliable technique for analyzing glycan structure. PBC patients positive for different autoantibody exhibits distinct glycan profile. Altered levels of glycosylation may be related to the occurrence and development of the disease, which could provide a direction for new biomarker identification.